RELATIONAL DATABASE WORK OPTIMIZATION OF THE TRANSPORT INFORMATION SYSTEM (Transport systems and technologies, 2023)
Informatization of society poses new challenges and requirements for information systems in transport, which are responsible for data processing and storage. A significant number of performance problems in developed applications are related to databases, because often poor database performance directly affects the application's slowdown. For the normal functioning of the processes of diagnostics of rolling stock and automation systems, decision-making, and the formation of reports in the transport industry, the task of optimizing the management of databases and ensuring their productivity under the condition of simultaneous multi-user access arises. The article discusses the stages of query execution and approaches to increasing the efficiency of the query optimizer. The main factors that depend on the performance of queries in information systems based on relational databases are analyzed. Optimization criteria can include such performance estimates as time required to generate a report, query execution time, speed of finding data in non-indexed fields, maximum number of simultaneous accesses to data in multi-user mode, speed of indexing, as well as update, delete and add operations.
Keywords: relational databases, information systems, query optimization, database management systems, SQL.